Has Mexico City’s shift to commercially produced housing increased car ownership and car use? - Erick Guerra (Journal of Transport and Land Use)
Mexico City’s principal form of housing production has shifted over the past two decades. More households now purchase houses in large commercially built housing developments than move into informal settlements. Looking at 1500 households in two suburban municipalities from a 2007 metropolitan travel survey, this study is the first to quantify differences in car ownership and car use across households in informal settlements and commercial housing developments. Accounting for income, proxies for wealth, household composition, and geography, households living in commercial housing developments are likely to own more cars and drive more than similar households in neighboring informal settlements. A test for residential self-selection finds no unobserved correlations across households that own cars and live in commercial housing developments, suggesting that the included controls do a good job of capturing the effects of residential self-selection or that the effects are limited. Something about the local land use and design of new commercial housing developments appears conducive to car ownership and use. Differences between the two settlement types, including more parking, wider streets, less-connected street-grids, and less accessible transit stops in commercial settlements, likely play a role.